The Role of Learner Identity/ Self-guides and Agency in Learning English as a Foreign Language: The Stories of Two English Learners at the Higher Institute of Language in Tishreen University (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The general focus of the present article is on two interrelated concepts, that is, identity and agency and their role in learning English as a foreign language.An examination of the language education literature would reveal that there is a division between the post-structuralist concept of identity which gives primacy to the contextual influences that shape how we conceive ourselves, our relationships with the world around us and how we behave, and the psychologically oriented self-guides theory with its focus on the individual and on human behavior as being guided by some inner visions that individuals have of themselves and the world around them.Therefore, the present study suggests an analytical framework that combines those two perspectives and shows that individual agency in life in general and in language learning in particular is restricted both externally and internally. This is achieved through the analysis of the life stories and learning behaviors of two language learners at the higher institute of language in Tishreen University.